The Role of Policy and Regional Leadership in Job Motivation Among Generation Z Awareness - Fadillah, Hafiz; Rizky, M. Chaerul; Setiawati, Andini; Yana, Melody Try; Sandrinaya, Cinta Maulida (Research Horizon, 2025)
The high unemployment rate among Generation Z Awareness shows the need for adaptive regional policies and leadership in shaping the work motivation of the younger generation. This study aims to analyze the influence of the role of policy, regional head leadership, and motivation on the character and work readiness of Generation Z. The method used is quantitative with a survey design of 44 Gen Z respondents, who were selected purposively. The research instrument in the form of a questionnaire was tested for validity and reliability, with a Cronbach's Alpha value of 0.895. Data analysis was carried out using multiple linear regression and Pearson correlation through SPSS version 22. The results of the study show that the three variables the role of policy, regional head leadership, and motivation have a positive and significant effect on Generation Z Awareness. The role of inclusive and participatory policies forms a conducive work ecosystem, while the transformational leadership style of regional heads is proven to be a dominant factor in encouraging the enthusiasm and loyalty of Gen Z. On the other hand, intrinsic motivation supported by a work environment that is responsive to basic psychological needs also enhances the productive and adaptive work character of Gen Z. These findings underscore the importance of synergy between policy, leadership, and motivation in developing the younger generation.